Penerapan Prinsip-Prinsip Ekonomi Syariah Pada Pasar Tradisional Di Kota Bengkulu - Nauli, Roma Dona; Yuneri, Winda; Hartini, Kustin (Pakis Journal Institute, 2024)
Every step in the production chain must adhere to sharia ideals and principles in order for producers to fulfill their duty to optimizing benefits. Avoiding forbidden items in transactions and applying the suggested Islamic standards are the primary Islamic values in manufacturing. The purpose of this study is to determine and examine how sharia principles such as fairness, openness, and the proscription of usury are applied in typical market transactions. This study employed a qualitative methodology, gathering data through observations and interviews at a number of conventional marketplaces. The study's findings indicate that traditional and contemporary markets are essentially the same, with the only exception being the manner in which transactions take place. Traditional markets serve as both a tangible representation of the variety of the Indonesian people and a tiny version of their cosmopolitan society. Through just and honest dealings, markets in Islam seek to bring about wealth for both the earth and the hereafter (Al-Falah). As a result, Islam differs from other economic systems in a number of ways. Many traders from different areas have incorporated sharia economic ideas into their conventional market trading activity in Bengkulu. In this instance, the government's participation is crucial in educating traders about sharia economic principles, particularly in traditional marketplaces, in order to build a thriving economy founded on people's honesty and justice.